Capacity Building for MSMEs Through the Digital Market Ecosystem Strategy of the Mulyasari Social Forestry Business Group: Peningkatan Kapasitas UMKM Melalui Digital Market Ecosystem Strategy Kelompok Usaha Perhutanan Sosial Mulyasari - Fitra Jaya; Sucipto, Sucipto; Yati, Yati; Kadarisman, Kadarisman; Romi Siswanto; Nisa A’rafiyah Tri Wulandari; Siti Utami Dewi Ningrum (Universitas Lancang Kuning, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in Indonesia’s economy but continue to face various challenges, particularly in accessing digital markets. This Community Service Program (PkM) aims to enhance MSME capacity through the Digital Market Ecosystem strategy, with a case study on the Social Forestry Business Group (KUPS) Mulyasari. The method employed is a service learning approach based on experiential learning, involving needs analysis, socialization, training, mentoring, and program evaluation. The results indicate an increased understanding of digital market ecosystem concepts, digital marketing strategies, and digital financial systems among participants. Specifically, 80% of participants were able to explain the key components of the Digital Market Ecosystem, 90% understood its benefits, and 70% could select suitable digital platforms for their products. Furthermore, 90% of participants had active accounts on marketplaces or business social media, and 85% could utilize digital payment applications. The implementation of digital marketing positively impacted MSME visibility and operational efficiency. This program demonstrates that digital transformation can enhance MSME competitiveness in an increasingly dynamic business ecosystem.